2017
DOI: 10.1111/cdep.12273
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for Low‐Income Children in an Era of Increasing Income Inequality

Abstract: Children growing up in poverty are at heightened risk for poor health. Researchers have identified some mechanisms responsible for this association but we know less about how children are affected by growing up in communities, schools, and countries with varying levels of income inequality. In this article, we summarize what is known about the association between children's well‐being and income inequality, and outline three challenges that increasing levels of income inequality may pose to children from low‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…In terms of PD, adolescents from the poorest families (lowest-20% income group) suffered the most from income inequality. This finding supports previous studies showing that individuals with lower status in their communities experience stress and negative emotions due to unfavorable social comparisons (Odgers & Adler, 2018;Wilkinson & Pickett, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…In terms of PD, adolescents from the poorest families (lowest-20% income group) suffered the most from income inequality. This finding supports previous studies showing that individuals with lower status in their communities experience stress and negative emotions due to unfavorable social comparisons (Odgers & Adler, 2018;Wilkinson & Pickett, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Young people growing up in Britain and other high-income countries are facing unprecedented barriers to mobility during the transition to adulthood: educational debt, average age of first home ownership over 30 y, fluctuating wages, and high rates of insecure employment (the so-called "precariat") (17). Growing levels of inequality and low expectations of social mobility are also posing a threat to population health (18) and to child and adolescent health more generally (19). Inequality has been shown to weaken people's beliefs in socioeconomic opportunity, which in turn reduces the likelihood that young people will engage in behaviors that promote social mobility (20).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we found that it was specifically participants' perceptions of inequality between the top and the rest of the wealth distribution-between the "rich and the rest" (Odgers & Adler, 2018)-that were significantly correlated with their beliefs about mobility. In other words, the more participants perceived inequality to be extreme, such that the great majority of their society's wealth was concentrated among a small minority of the population-which the form of inequality that currently exists in America (Saez, 2016;Stone et al, 2018; Wolff, 2017)-the more likely they were to believe that the socioeconomic position an American is born into is the position that they are likely to stay in for life.…”
Section: Discussionmentioning
confidence: 80%
“…These findings may help inform our understanding of the psychological pathways by which inequality can affect important lifetime and societal outcomes. Theorists have speculated that as a result of the disparities it creates in more versus less advantaged individuals' access to resources and opportunities, high levels of economic inequality might lead disadvantaged individuals to believe that future socioeconomic success is unachievable for them (Browman et al, 2019a;Genicot & Ray, 2017;Kearney & Levine, 2016;McCall et al, 2017;Odgers & Adler, 2018;Sawhill & Reeves, 2016). In this way, in addition to the real opportunity-based barriers to economic advancement that inequality imposes (Gilens, 2012;Hayes, 2014;Owens et al, 2016;Reardon, 2011;Reardon & Bischoff, 2011a, 2011bWatson, 2009), systemic inequality may also influence the perceived value of engaging in behaviors that are touted as pathways to future socioeconomic success (e.g., persisting in school; Browman et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation